1999
DOI: 10.3354/meps188207
|View full text |Cite
|
Sign up to set email alerts
|

Host recognition and possible imprinting in the anemonefish Amphiprion melanopus (Pisces:Pomacentridae)

Abstract: Many reef fish have strong microhabitat preferences when they settle to the juvenile population, and choices at h s time may influence fish survival. This is exemplified in anemonefishes (Family: Pomacentridae) that exhibit obligate symbiotic relationships with a restricted range of sea anemone species. This study examined how juvenile anemonefish Amphiprion rnelanopus select their host, and whether recognition and selection are me&ated by an imprinting-like mechanism. Specifically, we experimentally examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
69
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 21 publications
1
69
0
1
Order By: Relevance
“…water type, ambient sound, presence of conspecifics) (Arvedlund and Nielsen 1996;Arvedlund et al 1999;Ross et al 2007;Simpson et al 2008). Olfaction has been shown to be an important settlement and orientation cue in settlement-stage coral reef fish larvae (Arvedlund and Nielsen 1996;Arvedlund et al 1999;Arvedlund and Takemura 2006;Dixson et al 2008;Huijbers et al 2008;Lecchini et al 2005a;Lecchini et al 2005b;MillerSims et al 2011). Similar to the results of this study, Huijbers et al (2008) showed that the French grunt (Haemulon flavolineatum), which has a similar life history to P. auratus, had a significant orientation preference for water taken from seagrass habitat over other choices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…water type, ambient sound, presence of conspecifics) (Arvedlund and Nielsen 1996;Arvedlund et al 1999;Ross et al 2007;Simpson et al 2008). Olfaction has been shown to be an important settlement and orientation cue in settlement-stage coral reef fish larvae (Arvedlund and Nielsen 1996;Arvedlund et al 1999;Arvedlund and Takemura 2006;Dixson et al 2008;Huijbers et al 2008;Lecchini et al 2005a;Lecchini et al 2005b;MillerSims et al 2011). Similar to the results of this study, Huijbers et al (2008) showed that the French grunt (Haemulon flavolineatum), which has a similar life history to P. auratus, had a significant orientation preference for water taken from seagrass habitat over other choices.…”
Section: Discussionmentioning
confidence: 99%
“…Art = artificial seawater; Out = outside harbour; Harb ¼ harbour entrance; As ¼ Asian date mussel habitat; SG ¼ seagrass habitat; and ASG ¼ artificial seagrass water; n ¼ sample size; P ¼ probability of the data given the null hypothesis that there was no preference between the two water sources It has been often shown that settlement-stage fish select habitats according to their characteristics (e.g. water type, ambient sound, presence of conspecifics) (Arvedlund and Nielsen 1996;Arvedlund et al 1999;Ross et al 2007;Simpson et al 2008). Olfaction has been shown to be an important settlement and orientation cue in settlement-stage coral reef fish larvae (Arvedlund and Nielsen 1996;Arvedlund et al 1999;Arvedlund and Takemura 2006;Dixson et al 2008;Huijbers et al 2008;Lecchini et al 2005a;Lecchini et al 2005b;MillerSims et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is likely that for aquatic vertebrates, sound cues prevail over olfactory and visual cues when long distances are involved (Leis et al 1996), primarily because sound travels long distances through water , Montgomery et al 2006. Most research on orientation mechanisms in marine vertebrates, such as fishes, have focused on single sensory modalities (Basil et al 2000, Gerlach et al 2007, Huijbers et al 2008 or multiple modalities using non-conflicting cues (Arvedlund et al 1999, Brolund et al 2003, Hale et al 2009). However, little is known about the role of multimodality when it concerns conflicting cues.…”
Section: Introductionmentioning
confidence: 99%
“…A wellknown marine symbiosis is that between anemones and clown-fishes (e.g. [7]), popularized through the animated movie Finding Nemo. However, fishes also form symbiotic relationships with other taxa such as jellyfish, the pelagic relatives of anemones.…”
Section: Introductionmentioning
confidence: 99%